Somatic Embryogenesis in Peach-Palm (Bactris gasipaes) Using Different Explant Sources - Steinmacher, Douglas A. (2016)
Peach palm (Bactris gasipaes Kunth) is a member of the family Arecaceae and is a multipurpose but underutilized species. Nowadays, fruit production for subsistence and local markets, and heart-of-palm production for local, national, and international markets are the most important uses of this plant. Conventional breeding programs in peach palm are long-term efforts due to the prolonged generation time, large plant size, difficulties with controlled pollination and other factors. Although it is a caespitose palm, its propagation is currently based on seeds, as off-shoots are difficult to root. Hence, tissue culture techniques are considered to be the most likely strategy for efficient clonal plantlet regeneration of this species. Among various techniques, somatic embryogenesis offers the advantages of potential automated large-scale production and putative genetic stability of the regenerated plantlets. The induction of somatic embryogenesis in peach palm can be achieved by using different explant sources including zygotic embryos, immature inflorescences and thin cell layers from the young leaves and shoot meristems. The choice of a particular explant depends on whether clonal propagation is desired or not, as well as on the plant conditions and availability of explants. Protocols to induce and express somatic embryogenesis from different peach palm explants, up to acclimatization of plantlets, are described in this chapter.